(untitled) (Third Sector Social Economic Review, 2025)
Heightened environmental consciousness has spurred demand for sustainability-oriented financial instruments globally. This study investigates the performance of sustainability mutual funds traded on Turkey’s Electronic Fund Trading Platform (TEFAS) from 2022 to 2024, benchmarked against the BIST100 index. Performance is evaluated using the Sharpe ratio, Value at Risk (VaR90), and Maximum Drawdown (MDD) metrics, selected for their robust capacity to measure risk-adjusted returns, loss risk, and portfolio stability. The TOPSIS multi-criteria decision-making method ranks the funds, with criteria weights derived from the objective CRITIC method, which accounts for inter-criteria correlations. The aggregated performance of the funds is also compared to the BIST100 to assess overall trends. Findings indicate that sustainability funds generally exhibit superior risk-adjusted returns, reduced loss risk, and enhanced stability compared to the BIST100, although these differences are not statistically significant. TOPSIS rankings reveal heterogeneity in fund performance, with some funds demonstrating exceptional results and others underperforming. The findings underscore the risk-mitigation potential of environmental, social, and governance (ESG)-focused investments in Turkey, supported by growing sustainability awareness. The study advocates for standardized ESG frameworks, regulatory enhancements, and investor education to strengthen the adoption of sustainability funds, contributing to both academic discourse and practical investment strategies in emerging markets.